2017
DOI: 10.1037/pha0000112
|View full text |Cite
|
Sign up to set email alerts
|

Chronic corticosterone administration effects on behavioral emotionality in female c57bl6 mice.

Abstract: Understanding the pathophysiology of affective disorders and their treatment relies on the availability of experimental models that mimic aspects of the disease. Most of the studies on depressive disorders are conducted with male rodents, mostly because including females in protocols is more difficult. Indeed, there is a complex series of changes in the brain of females due to the estrous cycle, adding an important variability factor to the disease. However, twice as many women as men have a lifetime diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 65 publications
4
29
1
Order By: Relevance
“…Also, sucrose consumption patterns could not be attributable to estrous phase at test [phase F (3,25) = 0.39, p = 0.76] (Fig. 5g), in agreement with a recent report using other estrous assessment approaches (Mekiri et al, 2017). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Also, sucrose consumption patterns could not be attributable to estrous phase at test [phase F (3,25) = 0.39, p = 0.76] (Fig. 5g), in agreement with a recent report using other estrous assessment approaches (Mekiri et al, 2017). …”
Section: Resultssupporting
confidence: 92%
“…Prior low-dose CORT decreased sucrose consumption in females, an anhedonic-like consequence (see also Mekiri et al, 2017). Meanwhile, DPH increased consumption, an anti-depressant-like effect [interaction F (1,25) = 10.6, p = 0.003] (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The score results from the sum of the score of five different body parts: head, neck, dorsal/ventral coat, tail and fore-/hind paws. For each body part, a score of 0 was given for good state (smooth fur), 1 for moderate degradation (fur with some spiky patches) and 2 for unkempt coat (bad fur) (Mekiri et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, we show that RS-67,333 is an ineffective prophylactic in female 129S6/SvEv mice at the varying doses administered. Prophylactic efficacy of has shown that female C57BL/6NTac mice are insensitive to chronic CORT [46]. Future studies are necessary to determine the sex-and dose-specific effects of prophylactic compounds, as twice as many women as men have a lifetime diagnosis of MDD [47].…”
mentioning
confidence: 99%